A retrospective study of life skills promotes healthy Internet use among adolescents - Satish Kumar Ramakrishna; Mysore Narasimha Vranda; Manoj Kumar Sharma; Gobinda Majhi; Duraimurukan Gunasekaren; Radhakrishna Vasanthra Cicil (Journal of Family Medicine and Primary Care, 2023)
Background: Since the beginning of COVID-19 pandemic, studies highlight the augmentation in the use of Internet and smartphone, especially among the adolescents. However, little is known about the effect of technology addiction on adolescent mental health following reopening of the schools. Aim: The study aims to assess the level of technology addiction, life skills, and mental health impact among adolescents during the COVID-19 pandemic in India Materials and Methods: A cross-sectional research was conducted from July 2021 to October 2022. A nonprobability convenience sampling was used to collect the data from 352 adolescents using an Internet addiction test, smartphone addiction scale, life skills scale, and patient health questionnaire. Results: More than half of the adolescents were moderately addicted to the Internet and Smartphone. Three-fourth of the adolescents had mild-to-moderate depression. Those with moderate life skills were found to be moderately addicted to the Internet and Smartphone. Religion was found to be associated with Internet addiction. Age, religion, and parental monthly income were significantly associated with smartphone addiction among adolescents. Furthermore, class and life skills were significantly associated with depression among adolescents. Conclusion: Early-life skills training can help to prevent dysfunctional Internet use and mental and psychological problems among adolescents in schools and colleges.